Emerging applications of sludge biochar-based catalysts for environmental remediation and energy storage: A review. (1st August 2022) - Mian, Md Manik; Alam, Nur; Ahommed, Md Sohel; He, Zhibin; Ni, Yonghao
Abstract: The discovery of carbon-based catalysts triggers a wealth of research towards metal-free catalysis. Various low-cost and earth-abundant biomaterials have been investigated to produce carbonaceous catalysts as they are a natural source of carbon and other functional elements. In recent years, sludge biochar as a catalyst has received considerable research interest because of its promising performance in advanced oxidation processes (AOPs) and energy storage devices (ESDs). Besides, it offers a cost-effective and environmentally friendly sludge valorization method that develops environmental processes based on circular economic principles. In this review, we systematically summarized the state-of-the-art nature of this technology, including catalysts synthesis routes, physicochemical properties, and applications in AOPs and ESDs. A relationship between carbonization factors and the development of catalytically active sites is presented with an in-depth discussion. The advantages and disadvantages of different modification processes are highlighted. In addition, scientific insight is given into various catalytic mechanisms during their applications. Eventually, we have outlined the challenges and prospects of this emerging field. Along with covering the advances in this research, this review comprehensively documented the sludge biochar application in ESDs for the first time. Graphical abstract: Image 1 Highlights: The innate composition of sludge is beneficial for catalyst preparation. Sludge biochar engineering renders ultra-high surface area and rich active sites. Optimized sludge biochar performs promising catalysis reactions in AOPs and ESDs. Catalytic mechanisms and active sites' roles are elucidated. Challenges in SB-based catalysis can be overcome, and it has a bright future.